_ STRATEGI KOMUNIKASI KEPEMIMPINAN PT.TELKOM WITEL SOLO DALAM PENGIMPLEMENTASIAN CORE VALUE "AKHLAK" UNTUK MEMBANGUN MOTIVASI KINERJA: STRATEGI KOMUNIKASI KEPEMIMPINAN - Dewi Kurniasari, Agnes Berlian; Wangi, Maya Sekar; Aji, Haryo Kusumo; Suryo, Herning (Solidaritas, 2023)
Companies need human resources with quality performance whose role is tosupport the success of the company in achieving the vision and mission within thecompany environment. This requires someone who is given trust and has moreability to manage its members, which is called a leader. The figure of a leader is afactor in determining the productivity of his employees' performance. This isbecause the communication strategy carried out by leaders can motivate employeeson the quality of their performance. In implementing it, a leader at PT. TelkomWitel Solo has its own strategy so that all members can apply AKHLAK values inthe company environment in their daily activities to increase work motivation. Thisstudy aims to describe the Leadership Communication Strategy at PT. Telkom WitelSolo in Implementing AKHLAK's Core Values which is an acronym forTrustworthy, Competent, Harmonious, Loyal, Adaptive, Collaborative atPT.Telkom Witel Solo to Build Performance Motivation. This study used descriptivequalitative method. This study uses Harsey & Blanchard's Situational LeadershipTheory which divides into 4 styles namely Informing Leadership Style, SellingLeadership Style, Participating Leadership Style, and Delegating Leadership Style.The results of this study indicate that there is a communication strategy carried outby the leadership of PT. Telkom Witel Solo in implementing the AKHLAK corevalues to motivate the performance of its members, there is a strategy incommunicating in the leadership of PT. Telkom Witel Solo by applying SituationalLeadership Theory by Harsey & Blanchard. Suggestions that can be given byresearchers are leaders and all members of the company can have a communicationstrategy in establising cooperation to achieve the company’s vision and mission inimplementing AKHLAK core values in everyday life whitin the companyenviroment.Keywords: Leadership Communication Strategy, Core values of AKHLAK,Performance motivation.